CRISPR-Based Technologies for the Manipulation of Eukaryotic Genomes - Komor, Alexis C.; Badran, Ahmed H.; Liu, David R. (Cell, 2017)
The CRISPR-Cas9 RNA-guided DNA endonuclease has contributed to an explosion of advances in the life sciences that have grown from the ability to edit genomes within living cells. In this Review, we summarize CRISPR-based technologies that enable mammalian genome editing and their various applications. We describe recent developments that extend the generality, DNA specificity, product selectivity, and fundamental capabilities of natural CRISPR systems, and we highlight some of the remarkable advancements in basic research, biotechnology, and therapeutics science that these developments have facilitated. CRISPR-based genome-editing technologies provide powerful tools to study basic biology and may lead to new treatments for human disease.